Photodynamic effects of methylene blue-loaded polymeric nanoparticles on dental plaque bacteria - Klepac-Ceraj, Vanja (2011)
BACKGROUND AND OBJECTIVES: Photodynamic therapy (PDT) is increasingly being explored for treatment of oral infections. Here, we investigate the effect of PDT on human dental plaque bacteria in vitro using methylene blue (MB)-loaded poly(lactic-co-glycolic) (PLGA) nanoparticles with a positive or negative charge and red light at 665 nm. STUDY DESIGN/MATERIALS AND METHODS: Subgingival plaque samples were obtained from 14 patients with chronic periodontitis. Suspensions of plaque microorganisms from seven patients were sensitized with anionic, cationic PLGA nanoparticles (50 μg/ml equivalent to MB) or free MB (50 μg/ml) for 20 min followed by exposure to red light for 5 min with a power density of 100 mW/cm(2). Polymicrobial oral biofilms, which were developed on blood agar in 96-well plates from dental plaque inocula obtained from seven patients, were also exposed to PDT as above. Following the treatment, survival fractions were calculated by counting the number of colony-forming units. RESULTS: The cationic MB-loaded nanoparticles exhibited greater bacterial phototoxicity in both planktonic and biofilm phase compared to anionic MB-loaded nanoparticles and free MB, but results were not significantly different (p>0.05). CONCLUSION: Cationic MB-loaded PLGA nanoparticles have the potential to be used as carriers of MB for PDT systems.